Risk factors for tumors or leukemia development in the first two years of life - Wiedermannova, Hana; Mudry, Peter; Pavlicek, Jan; Tomaskova, Hana; Hladikova, Andrea; Palova, Hana; Vesela, Petra; Slaby, Ondrej; Sterba, Jaroslav (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2023)
OBJECTIVES: The objective of this study was to determine the incidence of neoplastic diseases and associated risk factors in the early stages of life. METHODS: Data were retrospectively assessed in 730,000 live births between 2000 and 2019. The occurrence of tumors was monitored in the neonatal, infant (1-12 months), and toddler (13-24 months) periods. Risk factors were divided into demographic, internal, and environmental factors. The control group consisted of subjects in the same age category without oncological diseases. RESULTS: A total of 452 neoplastic diseases were diagnosed in the study sample. In total, 24% (110/452) manifested during the neonatal period, 45% (203/452) in infants, and 31% (139/452) at the age of 13-24 months. Any genetic disease (OR 26.68; 95% CI 7.64-93.12) and medications used by the mother (OR 3.07; 95% CI 1.32-7.15) were identified as risk factors. Without adjustment for all factors, asphyxia in the first minute, a younger age of the mother, lower pregnancy, and the presence of a congenital defect manifested themselves as risk factors. CONCLUSIONS: The highest risk factors for the development of early childhood tumors were identified as with medications used by the mother before or during pregnancy and genetic diseases.
Keywords: Infant; neoplastic disease; nádory; těhotenství; předškolní dítě; retrospektivní studie; Humans; risk factors; leukemie; matky; Risk Factors; Leukemia; Child, Preschool; Infant, Newborn; rizikové faktory; Mothers; epidemiology; novorozenec; ženské pohlaví; lidé; early-aged period; Pregnancy; Neoplasms; Retrospective Studies; kojenec; Female